Leptin in Maternal Plasma and Cord Blood as a Predictor of Offspring Adiposity at 5 Years: A Follow‐up Study. Issue 2 (3rd December 2017) - Meyer, Dorothy Marie; Brei, Christina; Stecher, Lynne; Much, Daniela; Brunner, Stefanie; Hauner, Hans
Abstract : Objective: Perinatal leptin exposure may modulate the risk of adiposity in early childhood. In previous analyses, negative associations between maternal (32 weeks' gestation) and cord blood leptin and offspring body composition at 2 years were observed. Methods: Associations between maternal/cord blood leptin were assessed with indirect (i.e., body weight, BMI percentiles, sum of 4 skinfold thicknesses), and direct (i.e., ultrasonography, magnetic resonance imaging in a subgroup) growth and adipose tissue (AT) measurements in 120 children aged 3 to 5 years. Results: Maternal leptin was not shown to be associated with offspring body composition in univariate analyses. In adjusted analyses, some weak negative associations were observed with weight and BMI percentiles but not with sum of 4 skinfold thicknesses or calculated body fat at 3 to 5 years. Cord blood leptin was inversely related to offspring body composition, but effect sizes were small and not consistently statistically significant. No evidence of associations with direct AT measurements was observed. Conclusions: Although some negative relationships with indirect measurements of AT mass were observed, the results of this study do not provide sufficient evidence that maternal plasma or cord blood leptin is clinically relevant predictors of obesity or body fat distribution in early childhood.